Identificación de genes Cry1 en aislados de Bacillus thuringiensis y su efecto tóxico contra Milax gagates, plaga en lechuga (Lactuca sativa) (2018)
Milax gagates is one of the main pests in the cultivation of lettuce, causing considerable economic losses. Control with molluscicides totally or partially eliminates the pest but generates a negative impact on the environment due to their high toxicity. Biological management also allows controlling the pest, but in a specific and safe way for the environment. Therefore, the objective of this work was to evaluate the toxic effect of Bacillus thuringiensis, with Cry1 genes, against M. gagates by means of a bioassay. Seventy-five soil samples were taken from several municipalities in Norte de Santander, Colombia, from where 58 isolated colonies of B. thuringiensis with similar characteristics were obtained. Of these colonies, five showed the presence of Cry1 genes, and were those used in the bioassays together with the control B. thuringiensis var. Kurstaki. The treatments caused 90-100 % lethality to M. gagates at a concentration of 500 μg∙mL-1. The calculated LD99 suggests the use of 820 μg∙mL-1 of the biopreparate to obtain 100 % lethality with any of the five isolates studied.